2022
DOI: 10.3390/ijms232314733
|View full text |Cite
|
Sign up to set email alerts
|

Characterization in Potent Modulation on Voltage-Gated Na+ Current Exerted by Deltamethrin, a Pyrethroid Insecticide

Abstract: Deltamethrin (DLT) is a type-II pyrethroid ester insecticide used in agricultural and domestic applications as well as in public health. However, transmembrane ionic channels perturbed by this compound remain largely unclear, although the agent is thought to alter the gating characteristics of voltage-gated Na+ (NaV) channel current. In this study, we reappraised whether and how it and other related compounds can make any further modifications on voltage-gated Na+ current (INa) in pituitary tumor (GH3) cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Na + channels that have been opened in a voltage-dependent manner then shift to an inactive state, resulting in the transient enhancement of I Na . In addition to the voltage dependence of slow I Na inactivation, studies have reported the striking cumulative inhibition of the current activated during pulse train stimulation ( Taddese and Bean, 2002 ; Huang et al, 2015 ; Navarro et al, 2020 ; Lin et al, 2022 ; Wu et al, 2022a ). At present, it remains unclear whether and how CRS can interact with Na V channels to modify the magnitude, gating kinetics, and frequency-dependence of I Na .…”
Section: Introductionmentioning
confidence: 99%
“…Na + channels that have been opened in a voltage-dependent manner then shift to an inactive state, resulting in the transient enhancement of I Na . In addition to the voltage dependence of slow I Na inactivation, studies have reported the striking cumulative inhibition of the current activated during pulse train stimulation ( Taddese and Bean, 2002 ; Huang et al, 2015 ; Navarro et al, 2020 ; Lin et al, 2022 ; Wu et al, 2022a ). At present, it remains unclear whether and how CRS can interact with Na V channels to modify the magnitude, gating kinetics, and frequency-dependence of I Na .…”
Section: Introductionmentioning
confidence: 99%
“…Pyrethroids such as DLT and tefluthrin have been shown to modify the gating properties of voltage-gated Na + (Na V ) channels. In a recent paper by Lin et al [ 2 ], the investigators reappraised whether and how DLT and other related compounds could modify the magnitude and gating of I Na in GH 3 cells. DLT exposure produced a differential and dose-dependent stimulation of I Na(T) and I Na(L) ; consequently, the EC 50 value needed for DL-stimulated I Na(T) or I Na(L) was estimated to be 11.2 or 2.5 μM, respectively [ 2 ].…”
mentioning
confidence: 99%
“…In a recent paper by Lin et al [ 2 ], the investigators reappraised whether and how DLT and other related compounds could modify the magnitude and gating of I Na in GH 3 cells. DLT exposure produced a differential and dose-dependent stimulation of I Na(T) and I Na(L) ; consequently, the EC 50 value needed for DL-stimulated I Na(T) or I Na(L) was estimated to be 11.2 or 2.5 μM, respectively [ 2 ]. The I Na(L) augmented by DLT was attenuated through the subsequent addition of dapagliflozin or amiloride but not by chlorotoxin.…”
mentioning
confidence: 99%
See 2 more Smart Citations